2015
DOI: 10.1080/15226514.2015.1073667
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the PCB-degrading bacteriaMesorhizobiumsp. ZY1 and its combined remediation withAstragalus sinicusL. for contaminated soil

Abstract: A bacterial strain ZY1 capable of utilizing PCBs as its carbon source was isolated from the root nodules of Chinese milk vetch (Astragalus sinicus L.). The strain was identified as Mesorhizobium sp. according to its physiological-biochemical properties and the analysis of its 16S rRNA gene sequence. When the initial OD600 was 0.15, 62.7% of 15 mg L(-1) 3,3',4,4'-TCB in a liquid culture was degraded by Mesorhizobium sp. ZY1 within 10 days. Mesorhizobium sp. ZY1 also greatly increased the biotransformation of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Soil is an important indicator of environmental pollution in PAHs, which can be a long-term reservoir of organic compounds [31][32][33]. The state of soil PAH pollution has received increasingly more attention in recent years [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Soil is an important indicator of environmental pollution in PAHs, which can be a long-term reservoir of organic compounds [31][32][33]. The state of soil PAH pollution has received increasingly more attention in recent years [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…xenobiotic degradation ( Figure 3C), in the Rhizosphere and Bulk Soil than in the Control [29,30,31,32,33]. On the other hand, the Control microbial community was quite different from that of the planted plots and some genera such as Nitrososphaera (Archaea), Nocardioides (Actinobacteria) and Stereoidobacter (Gammaproteobacteria) were signi cantly more abundant than in the other condtions.…”
Section: Discussionmentioning
confidence: 92%
“…Inoculation with active ZY1 significantly degraded PCBs compared with control (P < 0.05). A remarkable enhancement in the total PCB degradation was also observed (57.6%) in the active inoculants treatment (Teng et al, 2016). Teng et al, (2016), reported that the bacterial inoculation significantly enhanced the numbers of bacteria able to use PCBs as the sole carbon source in the soil compared with control ( Fig.…”
Section: Treatmentsmentioning
confidence: 89%
“…With the degradation of tetra-CB, the proportion of tri-CB increased. The percentage of di-CB increased to 36.7% in the first 7 days and then decreased to 14.7 % at the 28th day (Teng et al, 2016). Teng et al, (2016), reported that the combined remediation effects of planting A. sinicus inoculated with Mesorhizobium sp.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation